Research on Antecedents of Residents’ Willingness to Cooperate in Urban Regeneration Projects: Based on an Extended Theory of Planned Behavior (TPB) Model - Dan Wang; Shouwen Jiang; Bingsheng Liu; Xinjian Li; Xiaohao Yuan (Buildings, 2022)
Residents’ willingness to cooperate can contribute to the success of urban regeneration projects worldwide. However, limited research has explored factors determining residents’ willingness to cooperate with neighborhood regeneration projects. This study aims to investigate the influence of psychological factors on urban residents’ willingness to comply with neighborhood regeneration projects. To achieve this goal, the study extends the theory of planned behavior by specifying the effects of perceived benefit, perceived risk, and perceived fairness on residents’ compliance intention toward neighborhood regeneration projects. Data from 362 local residents (i.e., homeowners) in China were analyzed using partial least squares structural equation modeling. Results show that perceived benefit, perceived risk, and perceived fairness have significant effects on the attitude, subjective norm, and perceived behavioral control, which in turn enhance residents’ compliance intention toward neighborhood regeneration projects. In addition, perceived benefit and perceived fairness also exhibit direct positive effects on residents’ compliance intention. This study develops an enriched model to examine the forming mechanisms of residents’ compliance intention under the context of neighborhood regeneration. It also provides more insights to enhance the decision-making regarding strategies of urban regeneration toward better social sustainability. Specifically, measures should be implemented to increase residents’ subjective norm, perceived behavioral control, and benefit perception. It is also recommended to foster a favorable attitude and to facilitate fairness perceptions of residents.